Jual Beli Lelang Berbasis Kearifan Lokal (Studi Desa Luat Lombang, Kecamatan Sipirok) - Tambunan, Jannus (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2020)
Sale and Purchase of Local Wisdom Based Wisdom (Study of Luat Lombang Village, Sipirok District) This article reviews the models of auction buying and selling in Luat Lombang Village community. For these people, buying and selling auction is no longer seen solely as a provision determined by religion, but has become a habit and need in community life. The approach method used in this article is the empirical juridical approach method, namely research on the effectiveness of law by studying legal regulations which are then linked to data and behavior that lives and develops in the midst of society. So the results of the study show that: First, the factors still carrying out the sale and purchase of auctions in the community of Luat Lombang Village, Sipirok District, because it has become a custom. Second, the sale and purchase of auctions to the public is done in cash, real and clear. Third, the legality of the implementation of buying and selling based on Islamic law in the community of Luat Lombang Village, Sipirok Subdistrict, is legal because it has fulfilled the legal requirements for the sale and purchase agreement and there are benefits for the buyer and the whole community can benefit from the sale of the auction.